The Reasons Behind Asymmetric Responses of Inflation to an Oil Price Shock Across the EU Members (Economic and Political Thought, 2014)
In this article, I have analysed the impact of an oil price shock on major EUeconomies and explained the reasons responsible for asymmetric responsesof inflation across members studied. The results of the study have much incommon with other similar research, however several findings still need to becited. First, oil intensity of the economy is not the main determinant of theimpact’s strength across the EU members. It is due to the fact that companiesobserved a substantial decrease in the relative oil usage in the productionprocess during past 30 years. This, together with low inflationary environmentand increased level of competition makes the adjustment of product pricesto the increased price of oil negligible and sometimes too costly. Second,the direct effect and consequently weight of fuel in HCPI is responsiblefor a significant share of cross-country differences. My study finds a strongrelation between the strength of the impact and HCPI’s structure, suggestingthat the pass-through is crucially dependent upon the households’ relativespending on fuels. Third, second-round effects cause another noticeable shareof differences across the EU members. Their strength is strongly correlatedwith the level of bargaining power employees have, supporting the initialhypothesis. In addition, the degree to which the effect of oil price shock isscattered over time is also affected by labour market flexibility level. Finally,the pass-through coefficients are relatively small, supporting Blanchard’s(2007) findings, which state that the effects of oil price change on inflationhave become relatively mild, compared to the 1960–1970s period.